2013
DOI: 10.5194/cp-9-1233-2013
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of climatic changes during the Holocene across the Italian Peninsula reconstructed from pollen data

Abstract: Lake-level records from Italy suggest that patterns of precipitation in the central Mediterranean during the Holocene were divided between the north and south, but a scarcity of reliable palaeoclimatic records in the north and central-southern Mediterranean means new evidence is needed to validate this hypothesis. We provide robust quantitative estimates of Holocene climate in the Mediterranean region using four high-resolution pollen records from northern (Lakes Ledro and Accesa) and southern (Lakes Trifoglie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 89 publications
3
110
0
3
Order By: Relevance
“…This discrepancy between the reconstructed SI from Hachlaf and the marine record may potentially be related to the fact that marine records collect pollen grains from a much wider geographical source area than continental (mountainous) records, which probably tends to smooth the local/regional changes. The reconstructed seasonality from the Italian records Peyron et al, 2013) is buffered by the less abrupt precipitation seasonal contrast at European temperate latitudes than at arid Mediterranean ones. SI was lower than 5 before 3750 cal BP despite an amount of precipitation between 600 and 700 mm yr −1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy between the reconstructed SI from Hachlaf and the marine record may potentially be related to the fact that marine records collect pollen grains from a much wider geographical source area than continental (mountainous) records, which probably tends to smooth the local/regional changes. The reconstructed seasonality from the Italian records Peyron et al, 2013) is buffered by the less abrupt precipitation seasonal contrast at European temperate latitudes than at arid Mediterranean ones. SI was lower than 5 before 3750 cal BP despite an amount of precipitation between 600 and 700 mm yr −1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, a change in the amplitude of SI has probably favoured those species best adapted to the length of the dry season, for instance evergreen oaks rather than deciduous. Pollen-based climate reconstructions from records collected in the Alboran Sea (Combourieu-Nebout et al, 2009) and Italy Peyron et al, 2013) suggest a rather steady and low seasonal contrast between P w and P s (about 2 times) over the past 6000 years. This discrepancy between the reconstructed SI from Hachlaf and the marine record may potentially be related to the fact that marine records collect pollen grains from a much wider geographical source area than continental (mountainous) records, which probably tends to smooth the local/regional changes.…”
Section: Discussionmentioning
confidence: 99%
“…This is the signature we see in the model simulations. The non-pollen proxy based palaeoclimatic data presented above and the pollen based reconstruction of Peyron et al (2013) rather support the differences in summer temperatures simulated by RCA3 than the PB reconstruction of Mauri et al (2013), in particular for southern and eastern Europe. For the winter temperatures, we have no appropriate non-pollen proxy based data to evaluate the RCA3 and PB results.…”
Section: Comparison Of the Rca3-simulated Regional Climate With Palaementioning
confidence: 92%
“…For the southern and eastern parts of the study area covered by the RCA3 simulations but not by the LANDCLIM database, we rely primarily on the non-pollen proxy-based climate reconstructions presented in , and in particular the synthesis of palaeohydrological changes and their climatic implications in the central Mediterranean region and its surroundings . The Mauri et al (2013) reconstruction in the Mediterranean area is also compared to the pollen-based climate reconstructions in the Mediterranean region published by Peyron et al (2013). The latter reconstructions are based on the multi-method approach that uses a combination of pollen-based weighted averaging, weighted-average partial least-squares regression, modern analogue technique (MAT), and non-metric multidimensional scaling/generalized additive model methods.…”
Section: Proxy Data Of Past Climatementioning
confidence: 99%
“…Renssen et al (2012) suggested that pollen-based temperature reconstruction may be unreliable since precipitation rather than temperature is the main climatic control on Mediterranean vegetation distribution, while Mauri et al (2015) argued instead that pollen transfer functions can provide robust results for temperature reconstruction in this region. Quantitative climate reconstruction methods have their own strengths and weaknesses Juggins and Birks, 2012), and pollen-based temperature reconstructions can show different patterns and amplitudes of change depending on the technique used Peyron et al, 2013). Deep Lake Ohrid, for which no major lake-level change during the Lateglacial and Holocene has been reported (Wagner et al, 2009;Reed et al, 2010), is arguably an ideal site for using palaeolimnological proxies such as diatoms to improve understanding of temperature change in this region.…”
Section: Introductionmentioning
confidence: 99%